Effects of Biofertilizer on Yield and Quality of Crops and Properties of Soil Under Field Conditions in China: A Meta-Analysis - Baolei Pei; Ting Liu; Ziyan Xue; Jian Cao; Yunpeng Zhang; Mulan Yu; Engang Liu; Jincheng Xing; Feibing Wang; Xuqin Ren; Zhenhua Zhang (Agriculture)
Biofertilizers play a crucial role in promoting sustainable agriculture in China; however, comprehensive quantification of their effects and limitations in field conditions remain unclear. In this study, a meta-analysis encompassing 1818 comparisons from 107 studies was conducted to quantify their systematic effects in field conditions in China. The results demonstrated that biofertilizers enhanced crop yields across 21 of the 23 investigated crops, with notable increases in millet (+65.42%), vegetables (e.g., Chinese cabbage +35.57%, ginger +39.18%), and legumes (kidney beans +54.03%), while cotton and rapeseed showed non-significant improvements. Nutritional quality was also improved, as evidenced by elevated levels of vitamin C (14.61%), protein (16.61%), and carotenoids (15.18%), alongside a reduction in nitrate content (21.94%). Soil health was significantly improved through increased organic matter (16.64%), enhanced enzymatic activities (urease: 57.60%; phosphatase: 43.51%), and a proliferation of beneficial microbes (bacteria: 157.10%; fungi: 30.28%), while pathogenic organisms were suppressed by 51.81%. The observed yield improvements were attributed to enhanced nutrient availability (total nitrogen: 16.67%; available phosphorus: 10.98%), optimized root growth (19.23% increase in volume), and a reduction in disease incidence (42.52%). The efficacy of biofertilizers was maximized when they were used in conjunction with organic amendments, resulting in a 29.20% increase in yield, particularly when applied prior to planting. These results show that biofertilizers boost productivity, quality, and soil functionality, depending on their production and field management practices. Their effectiveness is tied to optimizing soil properties and suppressing pathogens, providing strategies for sustainable agriculture in China.